Orogenic Segmentation and Its Role in Himalayan Mountain Building - Hubbard, Mary; Mukul, Malay; Gajurel, Ananta Prasad; Ghosh, Abhijit; Srivastava, Vinee; Giri, Bibek; Seifert, Neil; Mendoza, Manuel M. (Frontiers in Earth Science, 2021)
The continental collision process has made a large contribution to continental growth and reconfiguration of cratons throughout earth history. Many of the mountain belts present today are the product of continental collision such as the Appalachians, the Alps, the Cordillera, the Himalaya, the Zagros, and the Papuan Fold and Thrust Belt. Though collisional mountain belts are generally elongate and laterally continuous, close inspection reveals disruptions and variations in thrust geometry and kinematics along the strike of the range. These lateral variations typically coincide with cross structures and have been documented in thrust fault systems with a variety of geometries and kinematic interpretations. In the Himalaya, cross faults provide segment boundaries that, in some cases separate zones of differing thrust geometry and may even localize microseismicity or limit areas of active seismicity on adjacent thrust systems. By compiling data on structural segmentation along the length of the Himalayan range, we find lateral variations at all levels within the Himalaya. Along the Gish fault of the eastern Indian Himalaya, there is evidence in the foreland for changes in thrust-belt geometry across the fault. The Gish, the Ganga, and the Yamuna faults all mark boundaries of salients and recesses at the mountain front. The Benkar fault in the Greater Himalayan sequence of eastern Nepal exhibits a brittle-ductile style of deformation with fabric that crosscuts the older thrust-sense foliation. Microseismicity data from several regions in Nepal shows linear, northeast-striking clusters of epicenters sub-parallel to cross faults. The map pattern of aftershock data from the 2015 Nepal earthquakes has an abrupt northeast-trending termination on its eastern side suggesting the presence of a structure of that orientation that limited slip. The orientations of the recognized cross faults and seismic patterns also align with the extensional zones to the north on the Tibetan Plateau and the Indian basement structures to the south. Results from multiple studies are consistent with a link between cross faults and either of these structural trends to the north or south and suggest that cross faults may play a role in segmenting deformation style and seismic activity along the length of the Himalaya.